AN ANALYSIS OF SARAH KANE’S BLASTED AS A WORK OF IN-YER-FACE THEATRE - Ayyıldız, Nilay Erdem (My University, 2019)
Sarah Kane is one of the most significant playwrights of the 1990s’ in-yer-face theatre. Kane, who believes in the power oftheatre in changing people’s lives, aims to shake the audiences’ senses not to remain silent about the unpleasant eventsaround them. In this sense, her Blasted is an achievement. The play exemplifies all features of in-yer-face theatre. By examiningBlasted, the study aims at indicating how in-yer-face theatre makes the spectators face the things which are unsaid andconcealed. Through its vulgar language, sexuality, violence, and atmosphere constructed with catastrophic plots on the stage,the play violates a lot of conventional theatrical features and breaks all taboos.
Keywords: Edebiyat; Tiyatro; Edebi Teori ve Eleştiri